The new look on the latex allergy; risk groups, clinical manifestation, diagnosis, prevention - Romańska-Gocka, Krystyna; Gocki, Jacek; Zegarska, Barbara; Uchańska, Grażyna; Placek, Waldemar (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
In this review we present the newest data concerning the prevalence of latex allergy in high-risk populations in highly developed countries and in Poland. The prevalence of latex allergy in Western Europe and in the USA is systematically decreasing because of prevention programme and reduction of exposure to powdered high-protein latex gloves. Nowadays, in the mentioned countries, latex allergy develops among people from different than health care workers risk groups. In contrary, in Poland latex allergy remains still the severe problem, especially in the surgical departments employees. Moreover, in our country, only a few epidemiological studies on latex allergy were performed and we have not in our country the prevention programme for risk group patients, especially atopic patients. In the paper the possible genetic susceptibility to latex allergy was underlined. The clinical manifestations, the currently used diagnostic algorithm and the possible prevention methods for latex allergy were described too.